2002
DOI: 10.2214/ajr.179.5.1791209
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Shunts in Patients with Chronic Thromboembolic Pulmonary Hypertension: Evaluation with Helical CT and MR Imaging

Abstract: MR imaging was able to reveal substantial differences in flow between the systemic arterial and pulmonary venous circulations in patients with chronic thromboembolic pulmonary hypertension. These differences correlated well with the diameters of the bronchial arteries seen on helical CT. Furthermore, these differences resolved after pulmonary thromboendarterectomy. MR imaging enables the accurate estimation of flow in the bronchial arteries in patients with chronic thromboembolic pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 29 publications
0
61
0
1
Order By: Relevance
“…The severity of collateral development has only been assessed by angiographic visualization at cardiac catheterization, which is not a quantitative method. PCMR has been used to measure systemic collateral arterial flow to the lungs noninvasively by calculating the difference between ascending aorta flow and pulmonary artery flow (18). However, this method is not applicable in patients with bidirectional cavopulmonary anastomosis or when there is an intracardiac shunt.…”
Section: Clinical Applications Of Mr Quantification Of Pulmonary Venomentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of collateral development has only been assessed by angiographic visualization at cardiac catheterization, which is not a quantitative method. PCMR has been used to measure systemic collateral arterial flow to the lungs noninvasively by calculating the difference between ascending aorta flow and pulmonary artery flow (18). However, this method is not applicable in patients with bidirectional cavopulmonary anastomosis or when there is an intracardiac shunt.…”
Section: Clinical Applications Of Mr Quantification Of Pulmonary Venomentioning
confidence: 99%
“…In fact, systemic collateral arterial flow volume can easily be calculated by subtracting the pulmonary arterial flow volume from the pulmonary venous flow volume (Qspa ϭ Qpv Ϫ Qpa). Accurate measurement of systemic collateral flow to the lungs is also useful in differentiating secondary from primary pulmonary hypertension (16,18,19).…”
Section: Clinical Applications Of Mr Quantification Of Pulmonary Venomentioning
confidence: 99%
“…2,3 As the finding of dilated BAs is rarely seen in patients with idiopathic pulmonary arterial hypertension (PAH) or acute pulmonary embolism, it has been suggested that this feature could help distinguish patients with CTEPH from those with other diseases causing pulmonary hypertension. 1,3,4 The presence of dilated BAs represents increased systemic collateral blood supply 1,2 and it plays a important role in maintaining the viability of ischemic lung parenchyma after pulmonary artery occlusion. 5 However, the mechanisms of bronchial arterial development are not well understood.…”
mentioning
confidence: 99%
“…1 d). There may be significant systemic to pulmonary shunting, as systemic artery circulation in these cases not only supports the lung parenchyma, but also participates in blood oxygenation [32,33]. However, the detection of dilated systemic arteries is not a specific sign in patients with CTEPH as it may also be present in other forms of PH.…”
Section: Macrocirculationmentioning
confidence: 99%